Surgical Treatment of Sinonasal Mucosal Melanoma in Patients Treated with Systemic Immunotherapy - Chao, Tiffany N.; Kuan, Edward C.; Tong, Charles C. L.; Kohanski, Michael A.; Grady, M. Sean; Palmer, James N.; Adappa, Nithin D.; O'Malley, Bert W., Jr. (Journal of Neurological Surgery Part B: Skull Base, 2020)
Objective Surgical resection is widely accepted as a critical component for definitive treatment of sinonasal mucosal melanoma. Systemic immunotherapy, including multiple newer agents, has been used to treat metastatic or unresectable disease. In this study, we examine its efficacy in locoregional control when used in conjunction with surgical resection for primary mucosal lesions.Design Present study is a retrospective review of all patients at a tertiary academic medical center with primary sinonasal mucosal melanoma and distant metastatic disease.Results A total of four patients were identified. In all cases, patients were treated with a combination of surgical resection of the primary tumor and systemic immunotherapy. Three patients were initially treated with surgery at the primary site followed by immunotherapy for distant metastases. Response to immunotherapy at the sites of primary and metastatic disease was seen in two patients. All four patients developed progression or recurrence at the primary site following initiation of immunotherapy for which they underwent surgical resection. One patient remains in follow-up without evidence of disease 20 months after initial treatment; three succumbed to the disease at 135, 37, and 16 months after initial treatment.Conclusion Surgical resection for local control plays a critically important role in the treatment of sinonasal mucosal melanoma regardless of the presence of metastases and whether immunotherapy will be given. This case series suggests that, though immunotherapy may demonstrate efficacy in managing distant disease, surgery should remain the first-line treatment for the primary site.
Keywords: mucosal melanoma; sinonasal malignancy; endoscopic skull base surgery; immunotherapy